Newspaper representations of the psychological profile of domestic violence : an archival study - Mashabela, Raisibe Promise (University of Limpopo, 2015)
The aim of the study was to explore the psychological profiles of perpetrators of domestic violence as represented in newspaper articles. An archival research approach was chosen as the appropriate design for the present study. The researcher accessed and studied all newspaper articles from two daily newspapers reporting on domestic violence over a two-year period (that is, from January 2011 up to December 2012). A total of 98 newspaper articles (sixty from the Sowetan newspaper, and 38 thirty eight from the Daily Sun newspaper) covering the period under review were retrieved. The data was captured on a self-developed data record sheet. The Statistical Package for Social Sciences (SPSS) was used to analyse the data. The results were analysed and presented using frequency tables, descriptive statistics and cross-tabulations. The results of the study showed that the majority of the victims of domestic violence were women with little education and skills. Assault, attempted murder and murder were found to be the forms of violence perpetrated against the victims. The majority of the perpetrators (70.4%) were males, with higher education and skills. Some of the perpetrators were represented in the newspaper articles as being emotionally troubled (69.4%), passively aggressive (11.2%), mentally disturbed (5.1%) and socially deviant (3.1%). The majority of the mental health problems that were associated with the perpetrators of domestic violence included depression, borderline personality and acute psychosis. A number of triggers were found to lead to domestic violence. These included family arguments, jealousy, substance abuse, and criminal behaviour. Based on the above results, the study is concluded by recommending anger and stress management as some of the programmes that the government could introduce to minimise domestic violence.
Thesis (M.A. (Psychology)) --University of Limpopo, 2015
Keywords: Newspaper articles; Domestic violence; Mass media -- psychological aspects; Family violence